2021
DOI: 10.37741/t.69.4.8
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Study on Eye-Tracking Research in Tourism

Abstract: The purpose of this paper is to determine the position of eye-tracking studies in the tourism literature and to provide a panoramic perspective of social and intellectual structures of eye-tracking studies in tourism. Bibliometric methods have been used to analyze 64 studies published from 2013 – 2019. Descriptive, network, and cluster analyses were applied in the R statistics program. The annual growth rate on eye-tracking research in tourism was 38.31%. Most of the authors preferred to cite articles from tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…For systematic reviews , Scott et al [ 13 ], Atabay and Güzeller [ 14 ], and Savin et al [ 8 ] assessed the application of ET in tourism research. Meanwhile, Li et al [ 15 ] investigated the use of EEG in tourism and hospitality studies.…”
Section: Resultsmentioning
confidence: 99%
“…For systematic reviews , Scott et al [ 13 ], Atabay and Güzeller [ 14 ], and Savin et al [ 8 ] assessed the application of ET in tourism research. Meanwhile, Li et al [ 15 ] investigated the use of EEG in tourism and hospitality studies.…”
Section: Resultsmentioning
confidence: 99%
“…It provides an overview of the themes and their network representing the cognitive structure (Zupic & Čater, 2014). The use of software analysis coupled with the web of science database provides a systematic and objective approach to the literature on the topic (Atabay, & Güzeller, 2021). Figure 1 shows the flow of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Applying the authorship attribution method allows us to feature specific segments of an article to individual authors to analyze scientific authorship at a more fine-grained level [64]. Collaboration among authors is essential in research production [65], [66]. Arya and Sharma [67] found that the main factors in research productivity are collaborative research and authorship.…”
Section: Authorship Patternmentioning
confidence: 99%